Діагностика міри вираженості рефлексивності в майбутніх соціальних педагогів - Гунько, Степан; Gunko, Stepan (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті йдеться про результати діагностики рефлексивності студентів спеціальності «Соціальна педагогіка» Східноєвропейського національного університету імені Лесі Українки.В статье раскрываются результаты изучения актуального состояния развития рефлексивности у студентов специальности «Социальная педагогика» Восточноевропейского национального университета имени Леси Украинки. Установлено, что у большинства студентов низкий и средний уровень развития способности анализировать свои возможности при решении профессиональных задач; осуществлять поиск причинно-следственных связей в процессах и явлениях; реализовывать эффективное общение и взаимодействие с окружающими людьми; проектировать, прогнозировать и программировать свою профессиональную деятельность. Статистическими методами подтверждено, что между студентами младших и старших курсов существуют статистически достоверные различия, как за отдельными видами рефлексии так и в целом за уровнем развития рефлексивности.The article reveals the results of a study of the current state of development of reflexivity of the students from the specialty “Social pedagogy” of Eastern European National University named after Lesya Ukrainka. It was found that the majority of students have low and the average level of development of the ability to analyze their capabilities in solving of professional tasks; to search for causal relationships in the processes and phenomena; to implement effective communication and interaction with surrounding people; to design, to program and to predict their professional activities. The author with the help of statistical methods confirms that among students of junior and senior courses there are statistically significant differences as for certain types of reflection and as a whole by the level of reflexivity.
The Diagnostics of Reflexivity Expressiveness Measures of the Future Social Pedagogue.
Keywords: рефлексія, рефлексивність, діагностика рефлексивності; рефлексия, рефлексивность, диагностика рефлексивности.; reflection, reflexivity, diagnostics of reflexivity